Ustaw podane liczby w porządku rosnącym

b = -3 3/4 + 3 1/3 * (1 3/4 + 1/2)

c = -1 1/2 - 2 1/3 * (6/7 - 3)



Odpowiedź :

Enelo

Odpowiedź:

b = -3 i 3/4 + 3 i 1/3 * (1 i 3/4 + 1/2)

b = - 3 i 3/4 + 10/3 * (7/4 + 2/4)

b = - 3 i 3/4 + 10/3 * 9/4

b = - 3 i 3/4 + 5/1 * 3/2

b = - 3 i 3/4 + 15/2

b= - 3 i 3/4 + 7 i 1/2

b= - 3 i 3/4 + 7 i 2/4

b = 3 i 3/4

c = -1 i 1/2 - 2 i 1/3 * (6/7 - 3)

c = - 1 i 1/2 - 7/3 * (- 2 i 1/7)

c = - 1 i 1/2 - 7/3 * (- 15/7)

c = - 1 i 1/2 - 1/1 * ( - 5/1)

c = - 1 i 1/2 - (-5)

c = - 1 i 1/2 + 5

c= 3 i 1/2

Liczby w porządku rosnącym :

c = 3 i 1/2

b = 3 i 3/4

Szczegółowe wyjaśnienie: